2010
DOI: 10.1590/s1415-47572010005000059
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of cytochrome P450 1A1, glutathione s-transferases M1 and T1 genes in ouangolodougou (Northern Ivory Coast)

Abstract: In this study, the frequencies of CYP1A1, GSTM1, and GSTT1 gene polymorphisms were determined in 133 healthy individuals from Ouangolodougou, a small rural town situated in the north of the Ivory Coast. As appeared in several published studies, ethnic differences in these frequencies have been found to play an important role in the metabolism of a relevant number of human carcinogens. In the studied sample, the frequencies of Ile/Ile (wild type), Ile/Val (heterozygous variant), and Val/Val (homozygous variant)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
3
5
1
Order By: Relevance
“…The frequencies of GSTT1 deletion in our populations were higher than that described for Europeans, including British (18%) [20], French (16%) [21], German (13%) [22] and Austrian (20%) [23], as well as for other Middle Eastern populations, including Turks (17.3%) [24], and Iranians (21.2%) [25], but was significantly lower than SouthEast Asians, such as Chinese (56.5%) [26], Koreans (53.8%) [27] and Japanese (44%) [28]. The frequencies of GSTT1 null genotype in our Arab populations are similar to that of the sub-Saharan Africans: Zimbabweans (26%) [30], Gambians (37.1%) [31], Cameroonians (46.8%) [32] and Ivory Coast (33.1%) [33] (Table 2). The difference of GTSM1 and GSTT1 null alleles' frequency between our samples and those of others is attributed to their evolutionary histories, and also to selection arising from varied exposures to toxic substances.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The frequencies of GSTT1 deletion in our populations were higher than that described for Europeans, including British (18%) [20], French (16%) [21], German (13%) [22] and Austrian (20%) [23], as well as for other Middle Eastern populations, including Turks (17.3%) [24], and Iranians (21.2%) [25], but was significantly lower than SouthEast Asians, such as Chinese (56.5%) [26], Koreans (53.8%) [27] and Japanese (44%) [28]. The frequencies of GSTT1 null genotype in our Arab populations are similar to that of the sub-Saharan Africans: Zimbabweans (26%) [30], Gambians (37.1%) [31], Cameroonians (46.8%) [32] and Ivory Coast (33.1%) [33] (Table 2). The difference of GTSM1 and GSTT1 null alleles' frequency between our samples and those of others is attributed to their evolutionary histories, and also to selection arising from varied exposures to toxic substances.…”
Section: Discussionsupporting
confidence: 47%
“…Significant differences in GSTM1 null genotype distribution were seen with respect to Indians (20.7%) [29], and Africans, including Zimbabweans (24%) [30], Gambians (20.2%) [31], Cameroonians (27.8%) [32], and Ivory Coast (36.1%) [33] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The GSTT1 null allele frequency in Native Russians is very close to allelic frequencies observed in some European populations (Baysal et al, 2008). GSTT1 null allele in Ouangolodougou, a north Ivory Coast population, is significantly higher (33.1%) than in Chinese, Japanese and Pakistani populations (Santovito et al, 2010;Shaikh et al, 2010). In the HapMap CEU population, it was demonstrated that the SNP rs2266633 (Asp141Asn) is the "tagging SNP" of the GSTT1 homozygous deletion (Zhao et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…In this study, we found that the distribution of GSTM1-null, GSTT1-null, and GSTP1 in women and men were statistically comparable, p > 0.05 (Table 1). Santovito et al, reported similar results from north Ivory Coast regarding the distribution of GSTM1-null and GSTT1-null [24]. This finding may support the hypothesis that women and men probably have similar detoxification capabilities when exposed to xenobiotics.…”
Section: Discussionmentioning
confidence: 58%